Investigating the Problems Faced by Cancer Patients and the Management of These Problems: A Comprehensive Analysis of Predictions and Trends for the Healthcare Industry - Salgaonkar, Ashwini (Digital Repository of Theses, 2026)
Cancer remains a major global issue, affecting millions and putting enormous strain on healthcare systems. Despite advances in understanding the molecular and cellular causes of cancer, tackling its complexity and heterogeneity will require continued research. Aside from physical health, cancer patients confront a variety of issues, including psychological discomfort, dietary changes, financial difficulties, family mayhems, and limited access to healthcare resources. These challenges frequently increase the difficulties experienced by patients and their families, lowering their overall quality of life. The purpose of this study is to analyze the multiple challenges that cancer patients experience, as well as to assess the efficacy of current therapeutic options. A mixed- methods approach will be used to conduct quantitative surveys and qualitative interviews with adult cancer patients from various demographic backgrounds. The Biopsychosocial Model of Health serves as the foundation for the research, which looks at variables such as psychological stress, nutritional demands, financial difficulties, and healthcare access. The anticipated outcomes include identifying major obstacles and evaluating the efficacy of present care options. The findings aim to contribute to better patient care systems by providing practical recommendations to improve cancer patients’ quality of life and treatment outcomes while addressing important gaps in our overall understanding of their requirements